TXNDC12 knockdown promotes ferroptosis by modulating SLC7A11 expression in glioma - Yu, Hao; Zhu, Kai; Wang, Minjie; Jiang, Xiaobing (Clinical and translational science, 2023)
Ferroptosis is an iron‐dependent cell death process mainly triggered by reactive oxygen species (ROS) and lipid peroxidation. Thioredoxin domain protein 12 (TXNDC12) promotes the development of some tumors; however, its function in tumor ferroptosis remains unclear. In this study, we found that knockdown of TXNDC12 promoted erastin‐induced increase in ROS, lipid peroxidation, and Fe 2+ levels, and decreased glutathione content. TXNDC12 is involved in ferroptosis by regulating SLC7A11. Further studies showed that TXNDC12 knockdown promoted an erastin‐induced decrease in glioma cell viability. Overall, TXNDC12 played a significant role in ferroptosis by modulating SLC7A11 expression. Thus, TXNDC12 and ferroptosis may provide new targets for the treatment of gliomas.